Aislamiento de una cepa patógena de Leptospira spp del medio ambiente - Brihuega, Bibiana Felicitas; Hamer, Micaela; Esteban, Micaela; Saraullo, Vanina Rosa; Sanchez, Maria Cristina; Grune Loffler, Sylvia; Vilte, Daniel Alejandro; Martinez, Mara Leila (Universidad de Buenos Aires, 2025)
Poster